Synthesis of Renewable Triketones, Diketones, and Jet‐Fuel Range Cycloalkanes with 5‐Hydroxymethylfurfural and Ketones. Issue 4 (7th February 2017) - Li, Shanshan; Chen, Fang; Li, Ning; Wang, Wentao; Sheng, Xueru; Wang, Aiqin; Cong, Yu; Wang, Xiaodong; Zhang, Tao
Abstract: A series of renewable C9 –C12 triketones with repeating [COCH2 CH2 ] units were synthesized in high carbon yields (ca. 90 %) by the aqueous‐phase hydrogenation of the aldol‐condensation products of 5‐hydroxylmethylfurfural (HMF) and ketones over an Au/TiO2 catalyst. Compared with the reported routes, this new route has many advantages such as being environmentally friendly, having fewer steps, using a cheaper and reusable catalyst, etc. The triketones as obtained can be used as feedstocks in the production of conducting or semi‐conducting polymers. Through a solvent‐free intramolecular aldol condensation over solid‐base catalysts, the triketones were selectively converted to diketones, which can be used as intermediates in the synthesis of useful chemicals or polymers. As another application, the tri‐ and diketones can also be utilized as precursors for the synthesis of jet‐fuel range branched cycloalkanes with low freezing points (224–248 K) and high densities (ca. 0.81 g mL −1 ). Abstract : Green triketones : Renewable C9 –C12 triketones with repeating [COCH2 CH2 ] units are synthesized in high carbon yields (ca. 90 %) over a cost‐effective and reusable Au/TiO2 catalyst. The triketones as obtained can be used as feedstocks in the production of conducting or semi‐conducting polymers. Furthermore, they can also be converted to diketones or jet‐fuel range branched cycloalkanes with high densities and low freezing points.